ANALISIS PERLAKUAN AKUNTANSI SUMBER DAYA MANUSIA DALAM PEREKRUTAN TENAGA KERJA PADA PT. CATUR KARYA SENTOSA - Nurul Anisah Sihaloho; Facrul Rozi (Worksheet : Jurnal Akuntansi, 2022)
The purpose of this research is to determine the accounting treatment of human resources in recruiting workers. This study uses qualitative data analysis. The data used in this research are primary and secondary data. Data collection techniques used in this study were interviews and documentation. The results of this study are to show a comparison before and after the application of human resource accounting in the company's financial statements using conventional financial reports where human resource costs are still recognized as an expense, after the application of human resource accounting is recognized as an investment.